Construction and Validation of a Novel Pyroptosis-Related Four-lncRNA Prognostic Signature Related to Gastric Cancer and Immune Infiltration - Wang, Zhengguang; Cao, Lei; Zhou, Sitong; Lyu, Jin; Gao, Yang; Yang, Ronghua (Frontiers in Immunology, 2022)
Increasing evidence has demonstrated that pyroptosis, as a type of inflammatory programmed cell death, exerts an imperative role in the pathogenesis and progression of cancer. However, the studies focus on the application of pyroptosis-associated long non-coding RNAs (lncRNAs) in predicting stomach adenocarcinoma patients' prognosis remains unclear. The objective of this investigation was to examine and test the role of lncRNAs signature associated with the pyroptosis as a prognostic tool for gastric adenocarcinoma (STAD) and to ascertain their diagnostic and immune value. Methods: Relative RNA-sequencing data were extracted from TCGA and performed data preprocessing for STAD. Pearson correlation analysis was utilized to scour for lncRNAs significantly correlated to the pyroptosis process based on 23 genes related to the pyroptosis. Univariate Cox regression and Least absolute shrinkage and selection operator (LASSO) analyses were both adopted to select features and establish the pyroptosis-associated lncRNAs(PRLs) prognostic signature. Kaplan–Meier survival analysis of different risk groups was conducted according to the risk scores. We further examined the functional enrichment, tumor microenvironment, and the landscape of mutation status among different risk groups, and these analyses further explain the reasons for the differences in prediction as well as survival value of different risk groups. Results: Four lncRNAs, including HAND2-AS1, LINC01354, RP11-276H19.1and PGM5-AS1 were involved in the pyroptosis-related lncRNAs(PRLs) signature to split STAD patients into two risk groups. The high-risk group showed a poorer OS rate than the low-risk group in both the training set and testing set. Receiver operating characteristic (ROC) curves of PRLs were calculated to distinguish STAD patients from controls. Functional enrichment analysis and protein-protein interaction(PPI) of differentially expressed genes in the high- and low-risk groups were further employed to identify potential molecular functions and pathways associated with the pyroptosis process. In addition, there existed remarkable discrepancies between high- and low-risk groups in tumor stage (P < 0.01) and histologic grade(P < 0.05). Furthermore, drug-susceptibility testing indicated the potential sensitive chemo-drugs for each risk group. Conclusion: The current study established and validated a novel PRLs signature in STAD. It could act as a robust prognostic biomarker and serve as therapeutic guidance in clinical applications.